2004
DOI: 10.1063/1.1759071
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport through individual ZnO nanowires

Abstract: Electronic transport through individual ZnO nanowires has been investigated. The current increases linearly with the bias and the conductance jumps upon ultraviolet illumination. The increase rate upon the illumination is much faster than the decrease rate as the light is off. The decrease rate under vacuum is slower than that in air. These phenomena are related to the surface oxygen species and further confirmed by in situ current–voltage measurements as a function of oxygen pressure at room temperature. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
174
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(182 citation statements)
references
References 12 publications
6
174
1
1
Order By: Relevance
“…Schematics of the NW energy band diagrams in dark and under illumination are displayed in parts b and c of Figure 2, respectively, illustrating the charge separation process of photogenerated electrons and holes under the intrinsic NW electric field and the occupation of surface states by photogenerated holes. In ZnO, it has been previously shown that the following trapping mechanism is governing the photoconduction in thin films 25 and NWs: 8,9,13,18,[26][27][28] in the dark (Figure 2b), oxygen molecules are adsorbed on the oxide surface and capture the free electrons present in the n-type oxide semiconductor [O 2 …”
mentioning
confidence: 99%
“…Schematics of the NW energy band diagrams in dark and under illumination are displayed in parts b and c of Figure 2, respectively, illustrating the charge separation process of photogenerated electrons and holes under the intrinsic NW electric field and the occupation of surface states by photogenerated holes. In ZnO, it has been previously shown that the following trapping mechanism is governing the photoconduction in thin films 25 and NWs: 8,9,13,18,[26][27][28] in the dark (Figure 2b), oxygen molecules are adsorbed on the oxide surface and capture the free electrons present in the n-type oxide semiconductor [O 2 …”
mentioning
confidence: 99%
“…An alternative strategy is, first, to form the conductive metal electrodes on the insulating substrate of choice, and then to place the NRs/NWs on top of the electrodes so as to realize good ohmic contact between the ZnO and the electrodes. [15] Many prototype devices based on NRs/NWs have been reported, but the transfer and positioning of the NRs is too arduous for adoption in industrial applications. Harnack et al [16] demonstrated an electrical method of aligning semiconducting ZnO NRs onto pre-defined electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…This forms a low-conductivity depletion layer near the surface, where the screening of piezoelectric potential by free carriers effect is suppressed. [30,[32][33][34][35][36] This effect has been used to neglect free carriers in most simulation studies dealing with the piezoelectric response of semiconducting nanowirebased devices. A few papers have accounted for free carriers, although without account for SFLP.…”
mentioning
confidence: 99%